2022
DOI: 10.33369/jeet.6.3.310-326
|View full text |Cite
|
Sign up to set email alerts
|

EFL Pre-service Teacher’s Teaching Anxiety and the Coping Strategies during Teaching Practicum

Abstract: This research aims to investigate the sources of teaching anxiety as experienced by EFL pre-service teachers during the teaching practicum and the types of strategy used to cope with the teaching anxiety. This research used Aydin (2016) and Murray-Harvey et al. (2000) frames to investigate the sources of teaching anxiety and the strategies to cope with it. One English pre-service teacher was willing to participate as participant in this research. The data were collected through semi-structured interviews. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This strategy is also proven in research by Novitasari and Murtafi'ah (2022)-the results of this research state that institutional coping strategies can reduce pre-service teachers' anxiety. Preservice teachers greatly benefit from the guidance, encouragement, and advice their instructors provide, significantly aiding them in executing teaching duties during practical experiences.…”
Section: Institutional Strategymentioning
confidence: 73%
“…This strategy is also proven in research by Novitasari and Murtafi'ah (2022)-the results of this research state that institutional coping strategies can reduce pre-service teachers' anxiety. Preservice teachers greatly benefit from the guidance, encouragement, and advice their instructors provide, significantly aiding them in executing teaching duties during practical experiences.…”
Section: Institutional Strategymentioning
confidence: 73%
“…For instance, Ulfa and Sholah (2023) have explored the level of anxiety experienced by seventh-semester English students who are enrolled in teaching practicum. The study showed that they have perceived low to high anxiety levels, with some contributing factors such as a lack of teaching experience (Novitasari & Murtafi'ah, 2022), poor self-confidence, and limited vocabulary (Ulfa & Sholah, 2023) fear of receiving a poor grade, lack of enthusiasm from students, and a problem managing their time (Sari & Anwar, 2021). Djawamara and Listyani (2021) also found that instructional materials and lesson plans, as well as the methods used for conveying the content, become the source of their anxiety.…”
Section: Introductionmentioning
confidence: 97%
“…This interest crosses the boundaries of clinical psychology, the classroom, language classes, and more recently, foreign language classrooms (Kobul & Saraçoğlu, 2020;Li et al, 2023;Rani et al, 2022). a significant number of studies concentrated on the anxiety related to learning a foreign language, which is one of the important affective factors that may negatively affect people when learning a foreign language (Gorospe, 2022;Ismail et al, 2022;Novitasari & Murtafi'ah, 2022;Sari & Anwar, 2021). This feeling of anxiousness, which is a component of the affective filter, might discourage individuals from participating in a classroom (Djawamara & Listyani, 2021;Liu & Wu, 2021;Liu & Xiangming, 2019;Liu & Yan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations